Про один клас розкладних і фундаментальних інверсних моноїдів - Дереч, В.Д. (Український математичний журнал, 2013)
Пусть G — произвольная группа биекций на конечном множестве. Обозначим через I(G) множество всех частичных инъективных преобразований, каждое из которых включается в биекцию из G. I(G) является фундаментальной и разложимой инверсной полугруппой. В данной статье изучаются различные свойства полугруппы I(G). В частности, описаны автоморфизмы I(G) и найдены необходимые и достаточные условия для того, чтобы каждый стабильный порядок на I(G) был фундаментальным или антифундаментальным. Let G be an arbitrary group of bijections on a finite set and let I(G) denote the set of all partial injective transformations each of which is included in a bijection from G. The set I(G) is a fundamental factorizable inverse semigroup. We study various properties of the semigroup I(G). In particular, we describe the automorphisms of I(G) and obtain necessary and sufficient conditions for each stable order on I(G) to be fundamental or antifundamental.